A59 DECREASING HOSPITALIZATIONS AND SURGERIES IN CHILDREN WITH INFLAMMATORY BOWEL DISEASE: A POPULATION-BASED COHORT STUDY - Dheri, A (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Health services use in inflammatory bowel disease (IBD) patients cost the Canadian healthcare system $1.3 billion per year, but recent changes to care in children with IBD may have altered trends in health services use. Characterization of these trends would aid health policy makers plan for the healthcare needs of IBD children. AIMS: To quantify time trends in IBD health services use in children and all-cause health services use in children with and without IBD using a population-based cohort. METHODS: Using the Ontario Crohn’s and Colitis Cohort, children <18y with IBD diagnosed between 1994–2012 in Ontario were identified using validated algorithms from health administrative data, and matched on age, sex, rurality, and income to children without IBD. We evaluated trends in the number of IBD-specific and all-cause outpatient visits, emergency department (ED) visits, and hospitalizations using negative binomial regression. Cox proportional hazards regression models were used to describe changes in the hazard of intestinal resection (Crohn’s disease; CD) and colectomy (ulcerative colitis; UC) over time. Results are reported as annual percentage change (with 95%CI) for events within 5 years from the diagnosis/index date. RESULTS: IBD-specific hospitalization rates decreased by 2.5% (95%CI 1.8–3.2%) per year, but all-cause hospitalization rates in children without IBD decreased faster (APC, 95%CI: 4.3%, 3.5–5.1%, difference in rates p-value=0.0028). The hazard of intestinal resection for CD decreased by 6.0% (95%CI 4.6–7.3%) per year and the hazard of colectomy for UC decreased by 3.0% (95%CI 0.7–5.2%) per year. IBD-specific outpatient visit rates increased after 2005 by 4.0% (95%CI 3.1–4.9%) per year. Similar trends were not observed in children without IBD. CONCLUSIONS: Decreasing hazards of intestinal resection and colectomy in children with IBD suggest changes in disease management, including more care being provided on an outpatient basis. Decreased hospitalization rates in IBD were mirrored by similar decreases in non-IBD children, indicating universal care changes. Understanding why these trends are occurring may help us better understand how to provide optimal care to children with IBD. FUNDING AGENCIES: CIHRCanGIEC